Factors that enable the financial success of small enterprises in Peru - Wong, David; Ugarte, Dora (Universidad del Pacífico, 1995)
Small companies are successful to the extent that they know how to coordinate the factors that have a bearing on the achievement of their goals. By studying ten cases in depth, it was possible to establish that the overriding factors are the personal traits of the company´s founder, his operating values and availability of financial resources.